Melatonin attenuates chronic pain related myocardial ischemic susceptibility through inhibiting RIP3-MLKL/CaMKII dependent necroptosis. (December 2018) - Yang, Zheng; Li, Chen; Wang, Yishi; Yang, Jingrun; Yin, Yue; Liu, Manling; Shi, Zhaoling; Mu, Nan; Yu, Lu; Ma, Heng
Abstract: Chronic pain aggravates cardiovascular injury via incompletely understood mechanisms. While melatonin may participate in the pathophysiological process of chronic pain, its cardiovascular effects under chronic pain states remains unknown. In this study, chronic pain was induced by spared nerve injury model (SNI) for 4 weeks. We showed decreased the ipsilateral hind paw withdrawal mechanical threshold (PWMT) in SNI mice. High dose melatonin treatment (60 mg/kg, i.p.) could reversed nociceptive threshold in SNI mice. To verify the effect of chronic pain on the cardiac tolerance to ischemic stress, mice were subjected to myocardial ischemia-reperfusion (MI/R) in vivo. SNI mice showed exaggerated MI/R-induced detrimental effects and myocardial necroptosis compared with control group ( P < .05). Mechanically, an increased level of tumor necrosis factor-α (TNF-α) was found in SNI group following by a robust interaction of RIP1/RIP3. RIP3-induced phosphor-MLKL and CaMKII more significantly in SNI mice ( P < .05). We found that RIP3 deficiency provided a comparable protection against MI/R-induced necroptosis under chronic pain conditions. More importantly, low dose melatonin (20 mg/kg, i.p.) treatment 10 min before reperfusion decreased the level of TNF-α following with a negatively regulating the RIP3 induced phosphor-MLKL/CaMKII signaling, thus significantly reduced ROS production and cardiomyocyte necroptosis and ameliorated cardiac function. In summarize, our results demonstrated that chronic pain sensitizes heart to MI/R injury and myocardial necrosis plays an important role in this pathophysiological process. We also define melatonin acted as triple cardioprotective effects: ameliorating TNF-α level, suppressing RIP3-MLKL/CaMKII signaling induced necroptosis and exerting analgesia effect.